Kant’s Theory of Virtues and Doctrine of Rights Sanctioning Fair Business and Trade - Chris Abakare (HUMAN: South Asian Journal of Social Studies, 2021)
Trade and business have played a pivotal role in shaping the development of world’s economy and every home and individual is affected by it. The growth of every nation is largely controlled by its inherent capacity for smooth trade and business. Trade and Business contribute to the overall development of a nation by making a significant contribution in terms of tax revenues and providing lucrative employment. Thus, Trade and Business being such an important area of human concern cannot be given a free hand to govern and control the society. Business and trade are the potential forces of such a society endorsing peace and prosperity of every citizen provided they are properly steered. Therefore there is a need for a yardstick which would determine the worth and the depth of the business and trade policies. And, this yard-stick or standard by which we measure the reliability of the business and trade policies should be based on a solid philosophy. Due to the above, this research attempt to pinpoint the philosophy of Immanuel Kant, which I seek to unearth and recommend to the world of business and trade for the resolution of ethical conflicts.